Female university students' knowledge and practice of breast self-examination in Turkey - Koç, Gülten; Gülen-Savaş, Hacer; Ergöl, Şule; Yildirim-Cetinkaya, M.; Aydın, Nilgün (Medknow, 2019)
Breast cancer keeps its importance as an important health problem in developing countries like Turkey. Therefore, breast cancer screening and early diagnosis are more important for these countries. Although there are debates about breast self- examination, it is still involved in breast cancer screening programs in many countries.This study aimed to determine university students' knowledge and practice of Breast Self-Examination (BSE).The study universe consisted of all the female students studying at a public university. Sample size of 161 was calculated for a predicted event frequency. The research data were collected using a questionnaire.A total of 73.3% of the subjects students had heard about BSE. Only half of these students had obtained additional information about BSE. While half of the students indicated that they did perform BSE, 33.3% reported doing so at regular intervals. The majority of the students were aware of BSE and its purpose. Only about half stated, however, that they practice it. Those who practiced BSE were not knowledgeable about how and when to perform it.In developing countries, to have adequate knowledge of BSE of young women and to do BSE, it is important to develop a consciousness of breast health and an awareness of breast cancer at this age.
Keywords: Breast self-exam; knowledge; university student; Health Knowledge, Attitudes, Practice; Turkey; Universities; Breast Self-Examination; Breast Neoplasms; practice; Young Adult; female; Cross-Sectional Studies; Surveys and Questionnaires; Humans; Female; Students; Developing Countries; Early Detection of Cancer; 4. Education; 3. Good health